The Legionella pneumophila rpoS Gene Is Required for Growth within Acanthamoeba castellanii - Hales, Laura M. (American Society for Microbiology, 1999)
To investigate regulatory networks in Legionella pneumophila, the gene encoding the homolog of the Escherichia coli stress and stationary-phase sigma factor RpoS was identified by complementation of an E. coli rpoS mutation. An open reading frame that is approximately 60% identical to the E. coli rpoS gene was identified. Western blot analysis showed that the level of L. pneumophila RpoS increased in stationary phase. An insertion mutation was constructed in the rpoS gene on the chromosome of L. pneumophila, and the ability of this mutant strain to survive various stress conditions was assayed and compared with results for the wild-type strain. Both the mutant and wild-type strains were more resistant to stress when in stationary phase than when in the logarithmic phase of growth. This finding indicates that L. pneumophila RpoS is not required for a stationary-phase-dependent resistance to stress. Although the mutant strain was able to kill HL-60- and THP-1-derived macrophages, it could not replicate within a protozoan host, Acanthamoeba castellanii. These data suggest that L. pneumophila possesses a growth phase-dependent resistance to stress that is independent of RpoS control and that RpoS likely regulates genes that enable it to survive in the environment within protozoa. Our data indicate that the role of rpoS in L. pneumophila is very different from what has previously been reported for E. coli rpoS.